The short-term debt choice under asymmetric information - David Abad; Juan Pedro Sánchez-Ballesta; José Yagüe (SERIEs - Journal of the Spanish Economic Association, 2017)
This paper investigates whether the market level of information asymmetry affects firms' debt financing decisions. Using a sample of non-financial listed firms and a composite index based on microstructure measures of information asymmetry, we find that firms with more information asymmetry use shorter debt maturities. In addition, we find that these firms face more difficulties to access public debt and bank debt (particularly, short-term bank debt), and they have to rely on trade credit as an alternative source of short-term financing. Analyzing the associations in two subsamples based on firm size, we find that our results essentially driven by smaller companies, which are those affected by higher information asymmetries. Our findings support the information asymmetry theories of trade credit: as information asymmetry increases and, consequently, listed firms face more constraints in the credit markets, they increase the use of financing provided by their suppliers.
Keywords: G14; G32; 330; Information asymmetry; Market microstructure; Short-term debt; Bank debt; Accounts payable; Trade credit